PEMBERANTASAN MAFIA PERADILAN MENUJU REFORMASI HUKUM DI INDONESIA - C.Maya Indah S. (Masalah-Masalah Hukum, 2011)
"Judicial Mafia" is the same as with judicial corruption, and vis a vis with The Equality Before The Law principle. So, the access to Justice and fair treatment especially for marginal/poor society is only a myth . In realizing legal refonn, the public face of justice has role to eliminate it ,and concerns with Controlliability and responsiveness of law institutions, assault On Legal Exclusivism. Beside that, the Legal system isn't taken for granted, and research is aimed to study on how law are fonnulated, enforced, and administrated, and finally needs External Judicial control as a bottom up view's of law. Legal structure, legal substance , and legal culture refonn is reflected to realize the populis, moralis , transparent, and accountable in upholding of law.